Bone Marrow-derived Endothelial Progenitor Cell Intercellular Adhesion Assay - Yubo Tang; Angela Jacobi; Corina Vater; Xuenong Zou; Maik Stiehler (Bio-Protocol, 2016)
Cell-cell adhesion ensures tight contacts between neighbouring cells, which is necessary for cell segregation, as well as for the morphological and functional differentiation of different tissues. Evidently there are cell-cell recognition systems that make cells of the same type preferentially adherent to one another. Homotypic cell adhesion is particularly important in mediating a range of physiological processes such as cell survival, migration and remodeling of vessels. Thus in the present study we selected two populations of endothelial progenitor cells which are from the same donor to investigate the possible effect of a small molecule compound Icariin on homotypic cell adhesion. Many angiogenic factors can destabilize the organization of intercellular junctions, causing endothelial barrier opening. In the present study, we observed that Icariin treatment reduced the level of VE-cadherin expression in EPCs indicating a decrease in cell-cell adhesion-a proof of the pro-angiogenic effect of Icariin. In summary, the observed loss of homotypic adhesion of EPCs may contribute to the enhanced angiogenic effect exerted by Icariin.